Proceedings of the 37th IEEE Conference on Decision and Control (Cat. No.98CH36171)
DOI: 10.1109/cdc.1998.760800
|View full text |Cite
|
Sign up to set email alerts
|

A separation principle for the control of a class of nonlinear systems

Abstract: In this paper we give a general formulation of a number of control problems. This formulation considers a wide class of systems and any globally bounded state feedback controller that renders a certain compact set positively invariant and asymptotically attractive. We develop a converse Lyapunov theorem, and we prove that, by implementing the control law using a high-gain observer, we can recover asymptotic stability of the attractive set, its region of attraction, and trajectories.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
32
0
1

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(34 citation statements)
references
References 8 publications
1
32
0
1
Order By: Relevance
“…It was proved in [2] that the combination of high-gain observers with control saturation enables output-feedback control to recover the trajectories of its state-feedback counterpart if the observer gain is sufficiently high. For nonlinear systems with functional uncertainties, output-feedback approximation-based adaptive control (AAC) using high-gain observers and fuzzy systems/neural networks (NNs) has also been intensively studied [3]- [8] to overcome the limitations of state-feedback AAC [9]- [15].…”
Section: Introductionmentioning
confidence: 99%
“…It was proved in [2] that the combination of high-gain observers with control saturation enables output-feedback control to recover the trajectories of its state-feedback counterpart if the observer gain is sufficiently high. For nonlinear systems with functional uncertainties, output-feedback approximation-based adaptive control (AAC) using high-gain observers and fuzzy systems/neural networks (NNs) has also been intensively studied [3]- [8] to overcome the limitations of state-feedback AAC [9]- [15].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, Theorem 3 implies that the original uniformly asymptotically stable positively invariant set under state feedback is recovered, in the limit as E -+ 0, under output feedback. Furthermore, note that the implication of Theorem 3 is essentially identical to one idea found in [6]. This indicates that using an input derivative observer is advantageous in that, besides simplifying the controller design, in the presence of disturbance it yields the same stability results as when dynamic extension is employed at the input side of the system.…”
Section: (19)mentioning
confidence: 63%
“…This modification results in a simplification of the control design problem in that the original state feedback controller can be directly employed by the output feedback controller (i.e., , we eliminate the need to design a control law for the higher-order "extended system" in point 1 above). We prove that, in the presence of disturbances, this approach guarantees uniform ultimate boundedness (UUB) of the closed-loop system trajectories with respect to n/ (in complete analogy with the result of Theorem 4 in [6], but here we do not investigate conditions needed on the disturbance so that asymptotic stability is recovered). When no disturbance affects the system, it is shown that a design that is based on a sliding mode observer recovers the asymptotic stability of the closed-loop system with respect to N , while the high-gain observer achieves UUB.…”
Section: Introductionmentioning
confidence: 91%
See 2 more Smart Citations